The Relationship Between Optimism and Burnout In Rowing Athletes - Mitha Evalista; Yunus, Irfan (Indonesian Journal of Physical Activity, 2024)
This study aims to investigate the relationship between optimism and burnout in rowing athletes. The subjects in this study were 20 rowing athletes selected through purposive sampling technique. The research employed a quantitative method using optimism scale and burnout scale as measurement tools. The Spearman’s Rank Correlation Coefficient analysis technique was used, which revealed a correlation coefficient (r) of -0.880 with a significance level of 0.000 (p < 0.01). This indicates a negative relationship between optimism and burnout in rowing athletes; the lower the optimism of the athletes, the higher the burnout experienced. This study provides insight into the relationship between optimism and burnout, particularly how optimism can influence burnout